The Spirit of Human Rights: Universal Health Coverage in Makueni County, Kenya - Esther Kamau; Gillian MacNaughton (Health and Human Rights)
In view of the United Nations’ goal to achieve universal health coverage (UHC) by 2030, this paper investigates MakueniCare, the highly successful UHC program in Makueni County, Kenya, to reveal the spirit of human rights underlying it. Drawing on international, Kenyan, and Makueni County law and policy, as well as 30 interviews with government and civil society leaders in health care policy and programming at the national and county levels, we examine the human rights law and principles that underlie the adoption and implementation of MakueniCare. We first set out key human rights principles grounded in the International Covenant on Economic, Social and Cultural Rights and the 2010 Kenyan Constitution, and then describe the research design and methodology of the project. Then, we analyze the data collected to highlight the various ways in which the adoption and implementation of MakueniCare were influenced by human rights, particularly the right to health. We conclude with thoughts on how MakueniCare could be further improved from a human rights perspective.